KOMPOSISI MUSIK GODANG ONJAK - Uswatul Hakim; Syeilendra Syeilendra; Syahrel Syahrel (FBS Universitas Negeri Padang, 2013)
Abstract This thesis is aimed at raising the existence of Sampelong into a new form of work. It is because nowadays people are not really appreciative toward the traditional music, like Sampelong.In this musical work “Godang Onjak”, the writer wants to show that traditional music is not a monotonous music, but traditional music can be developed with different generated patterns and merged with other modern musical instruments. So, traditional music especially Logu sampelong art can be more attractive and acceptable to the public, especially the young generation. Thus, the traditional music will be more interesting and preserved by the next generation. Kata kunci : komposisi, Godang Onjak, Kesenian,Sampelong.